A study of unusual burns at a tertiary burn unit: a prospective study - Durairaj, Alagar Raja; Mahipathy, Surya Rao Rao Venkata; Ramachandran, Manimaran; Sundaramurthy, Narayanamurthy (International Surgery Journal, 2017)
Background: Unusual burns are not uncommon. They occur in the industrial as well as the domestic side. These are mainly burns due to chemicals, tar, fire walk and lightning burns. These burns occur as a result of improper handling of chemicals with poor safety measures or due to accidents. Here, we discuss about these burns, their epidemiology with treatment and preventive measures. Methods: The study was conducted at a tertiary care burn centre for a period of two years from Jan 2009 to Jan 2011. Forty-four patients with unusual burns were admitted and evaluated with a thorough history and clinical examination. Initial resuscitation was done followed by specific therapy in each of the cases. Results: The forty-four patients with unusual burns were categorized into chemical burns, lightning burns, tar burn, camphor burns, fire walk burns and miscellaneous types. These burns mostly involved adult males and were generally due to domestic reasons. 93% were due to accidents of which most of them were of the miscellaneous type (83%). Conclusions: Unusual burns are an important to know as these are occurring with regular frequency in the present days. These burns are usually accidental occurring in industries and in household setups. Proper education and safety measures could reduce the incidence of these unusual burns.